Heparin pre-treatment in patients with ST elevation myocardial infarction: a cohort study investigating the effects on coronary artery occlusion, mortality, and bleeding. (3rd October 2022) - Emilsson, O L; Bergman, S; Mohammad, M; Rylance, R; Olivecrona, G; Gotberg, M; Erlinge, D; Koul, S
Abstract: Background: Unfractionated heparin (UFH) is often administered before arrival at the cath lab in patients with ST-elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI). However, large studies regarding the clinical impacts of UFH pre-treatment are scarce. Purpose: To investigate if pre-treatment with heparin affects total coronary artery occlusion at angiography, mortality at 30 days, and major bleeding during hospitalization in patients with STEMI undergoing primary PCI. Methods: The study population was extracted from the SCAAR (Swedish Coronary Angiography and Angioplasty Registry) and consisted of unique patients with a first STEMI event undergoing PCI during the study period 2008 to 2016. Patients receiving UFH pre-treatment were compared with patients not receiving UFH pre-treatment. To obtain relative risks of the outcomes adjusted Poisson regression models with robust standard errors were used. In the adjusted models, we included age, sex, smoking status, year, comorbidities (as specified under tables 1 and 2), and anti-thrombotic treatment (as specified under tables 1 and 2). To obtain absolute risk differences, analyses of propensity score (PS) matched groups were performed. PS was based on the same variables as in the adjusted Poisson regression, and a caliper of 0.02 was used. Results: A total of 41, 631 patients were included in the study population (median age: 67 years; 71% male), with 16, 026 receiving pre-treatment with UFH and 25, 605 not receiving UFH pre-treatment. The adjusted Poisson model revealed that UFH pre-treatment was associated with an 11% relative risk reduction of coronary artery occlusion (95% confidence interval (CI): 9%; 12%), and an 13% (95% CI: 2%; 23%) reduced relative risk of mortality. For bleeding, no statistically significant difference was found. In the PS-matched analysis (median age: 67 years, 71% male), the absolute risk differences were for coronary artery occlusion 8.3% (95% CI: 7.1%; 9.5%) in favour of UFH pre-treatment, and for mortality 0.5% (−0.1%; 1.2%), with a modest trend in favour of UFH pre-treatment. For bleeding, no statistically significant difference was found. Conclusion: UFH pre-treatment was associated with a reduction in coronary artery occlusion at presentation at the cath lab in patients with STEMI, the number needed to treat being 13, without increasing the risk of bleeding. Regarding mortality, a reduced relative risk was found in the adjusted regression analysis, but the absolute risk difference was small and not statistically significant in the PS-matched analysis. Due to the retrospective study design, residual confounding cannot be excluded. Funding Acknowledgement: Type of funding sources: None.